MEDIASI PENAL DALAM PERKARA PIDANA SEBAGAI ALTERNATIF PENYELESAIAN PERKARA (STUDI KASUS TINDAK PIDANA PENCURIAN RINGAN DI POLRES KOTA MAKASSAR) - Setiyani, Dwi (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
Penal mediation is an alternative form of settlement of cases outside the court by prioritizing the principle of resortative justice which aims to achieve justice that is oriented towards improving the relationship between perpetrators and victims. This study aims to examine how the implementation and the obstacles faced by the Makassar City Police in conducting penal mediation in the settlement of minor theft cases. This research is a normative empirical research with a qualitative analysis approach. The result of the research obtained is that the implementation of penal mediation by the Makassar City Police in resolving minor theft cases is carried out based on police discretion as regulated by Law Number 2 of 2002 concerning the State Police of the Republic of Indonesia and Circular No. SE / 8 / VII / 2018 dated 27 July 2018 concerning the Application of Restorative Justice in the Settlement of Criminal Cases. The circular regulates how to apply the concept of restorative justice in solving criminal cases at the level of investigation or investigation in the police, while in its implementation there are still obstacles faced by the Makassar City Police, including emotional factors, namely the existence of selfishness between the perpetrator or victim justifying oneself and blaming the opposing party and financial (economic) factors, namely the inconsistency between the victim and the perpetrator to make peace, especially in matters of compensation.